ESTIMASI BATIMETRI DARI DATA SPOT 7 STUDI KASUS PERAIRAN GILI MATRA NUSA TENGGARA BARAT - Setiawan, Kuncoro Teguh; Manessa, Masita Dwi Mandini; Winarso, Gathot; Anggraini, Nanin; Giarrastowo, Gigih; Asriningrum, Wikanti; Herianto, Herianto; Rosid, Syamsu; Supardjo, A. Harsono (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2018)
Indonesia is an archipelagic state consists of five large islands and thousands of small islands surrounded by shallow marine waters. For this reason, complete and accurate bathymetric information is needed. Large scale bathymetry data in Indonesian waters is still limited, including in the shallow sea waters of Gili Matra, NTB Province. To overcome these problems, remote sensing technology is used. The aim of the study was to analyze the effect of shallow marine habitat base objects on estimating bathymetry from SPOT 7 satellite images. Many methods can be used to produce estimated bathymetry with this technology. The analysis used in this study is multiple linear regression (MLR). The data used is SPOT 7 satellite imagery in the shallow sea waters of Gili Matra, West Nusa Tenggara Province. The estimation of bathymetry was carried out using insitu depth data with two modifications. The first modification did not pay attention to the basic habitat object types and the second modification paid attention to the coral habitat, seagrass, macroalgae and substrate objects. The results of this study provide the value of determination R2 which increased from 72.1% to 78.6% and decreased the RMSE value from 3.3 meters to 2.9 meters.